The right to live in a healthy and safe natural environment - Krajewski, Piotr (Studia Ecologiae et Bioethicae, 2015)
The environment determines the existence of a man who nowadays is considered to be the main, sometimes the only protagonist of transformations. Man tied its existence with nature, depends upon it, but at the same time conditioned its existence from his good or ill will. He possess the tools and knowledge about the possibilities of its transformation and even annihilation. That is why he occupies a unique position in the universe. Efforts to protect the living environment must be multidirectional and coordinated. It is possible that in future modern biotechnology will be the solution for balanced development, which provides the possibility to exercise control over the economy and scientific research. Decision-making in this area involves the responsibility of international institutions, governments and citizens. Ergo, it is important that the development and use of modern technology, knowledge and skills, are performed in conditions which ensure maximum safety and without any rebounds to humans and their living environment.